103k views
2 votes
Let f(x) = -3x and g(x) = 2x-1
Find the following:
(fog)(1)

2 Answers

2 votes

Explanation:

steps are in picture above.

Note : if you have any confusion let me know.

Let f(x) = -3x and g(x) = 2x-1 Find the following: (fog)(1)-example-1
User Sam Adams
by
5.4k points
4 votes

9514 1404 393

Answer:

-3

Explanation:


(f\circ g)(1) = f(g(1)) = f(2\cdot1-1) = f(1)=-3\cdot1\\\\\boxed{(f\circ g)(1)=-3}

User Jayesh Bhoyar
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.